Defining the lipid profiles of human milk, infant formula, and animal milk: implications for infant feeding - George, Alexandra D.; Paul, Sudip; Wang, Tingting; Huynh, Kevin; Giles, Corey; Mellett, Natalie; Duong, Thy; Nguyen, Anh; Geddes, Donna; Mansell, Toby; Saffery, Richard; Vuillermin, Peter; et al. (Frontiers in Nutrition, 2023)
Background: Breastfed infants have lower disease risk compared to formula-fed infants, however, the mechanisms behind this protection are unknown. Human milk has a complex lipidome which may have critical roles in health and disease risk. However, human milk lipidomics is challenging, and research is still required to fully understand the lipidome and to interpret and translate findings. This study aimed to address key knowledge gaps and discuss possible implications for early life health. Methods: Human milk samples from two birth cohorts, the Barwon Infant Study (n=312) and University of Western Australia birth cohort (n=342), were analysed using four liquid chromatography-mass spectrometry (LC-MS) methods (lipidome, triacylglycerols, total fatty acids, alkylglycerols). Bovine, goat, and soy-based infant formula, and bovine and goat milk were analysed for comparison. Composition was explored as concentrations, relative abundance, and infant lipid intake. Statistical analyses included principal component analysis, mixed effects modelling, and correlation, with false discovery rate correction, to explore human milk lipidome longitudinal trends and inter and intra-individual variation, differences between sample types, lipid intakes, and correlations between infant plasma and human milk lipids. Results: Lipidomics analysis identified 979 lipids. The human milk lipidome was distinct from that of infant formula and animal milk. Ether lipids were of particular interest, as they were significantly higher, in concentration and relative abundance, in human milk than in formula and animal milk, if present in the latter samples at all. Many ether lipids were highest in colostrum, and some changed significantly through lactation. Significant correlations were identified between human milk and infant circulating lipids (40% of which were ether lipids), and specific ether lipid intake by exclusively breastfed infants was 200-fold higher than that of an exclusively formula-fed infant. Conclusion: There are marked differences between the lipidomes of human milk, infant formula, and animal milk, with notable distinctions between ether lipids that are reflected in the infant plasma lipidome. These findings have potential implications for early life health, and may reveal why breast and formula-fed infants are not afforded the same protections. Comprehensive lipidomics studies with outcomes are required to understand the impacts on infant health and tailor translation.